SOCIO-PSYCHOLOGICAL FEATURES OF PEDAGOGICAL TEAMS IN HIGHER EDUCATION - R. N. Melibayeva (Journals Park Publishing, 2025)
The socio-psychological makeup of pedagogical collectives in higher education institutions plays a pivotal role in shaping both the academic environment and the overall effectiveness of universities. This paper delves into the nuanced factors that underpin teamwork among university educators, considering how group cohesion, leadership practices, communication patterns, shared norms, and approaches to handling disagreements contribute to institutional performance. Fieldwork and literature analysis were carried out in Uzbekistan and compared with trends abroad. The results highlight that organizational culture, management approaches, and individual personalities all interact in complex ways to affect how well teams function and how satisfied their members feel. The study concludes by offering practical recommendations for university leaders and policymakers on building supportive, innovative, and resilient academic environments.
Keywords: Higher education, academic teamwork, psychological climate, faculty, organizational culture, group dynamics, university, Uzbekistan.